IMPACT ОГ DESFLURANE AND SEVOELURANE OH THE HEMODYHAMIC PROEILE IH THE PATIEHTS WITH DIRECT MYOCARDIAL REVASCULIZATION UHDER CARDIO-PULMОNARY BYPASS - N. S. Molchan; I. V. Shlyk; M. Yu. Sliiganov; A. E. Kobak; A. A. Khryapa (Вестник анестезиологии и реаниматологии)
Inhalation anesthetics of desflurane and sevoflurane when used in aortocoronary bypass with cardio-pulmonary bypass can reduce the frequency of post-perfusion heart weakness t h rough supporting stable hemodynamic profile of the patients undergoing cardiac surgery. 11 owever the choice between these two medications is often disputable. 43 patients with coronary disease who underwent direct myocardial revasculization with artificial cardio-pulmonary bypass were examined. Desflurane was used as a general anesthetic for 28 patients: sevoflurane was used for 15 patients. During surgery expanded hemodynamic profile data of all patients were evaluated (cardiac index - Cl. stroke volume index - SVI. medium blood pressure - МНР. index of general peripheral resistance - IGPR, index of systolic operation of the left anti right ventricles, pulmonary artery wedge pressure, index of pulmonary resistance) as well as oxygen transporting blood function (delivery, consumption and oxygen extraction co-efficient. oxygen arteriovenous difference) and arterial blood lactate level. The investigated data were recorded before artificial cardio-pulmonary bypass, after reperfusion of myocardium and upon anesthesia completion. Results. Both groups did not have any confident differences in МНР. pulmonary artery pressure, heart rate. In all examined patients С I increased significantly compared to pre-perfusion period due to the increase of stroke volume and systolic discharge of the heart ventricles. And sevoflurane caused more persistent reduction of IGPR after artificial cardio-pulmonary bypass compared to desflurane which required using angiotonic support in 41.1% of patients versus 3.4% of patients in the group where desflurane was used (2criterion with credibility correction, p< 0.01). The bigger need in oxygen when sevoflurane was used during the surgery (p < 0.01) was accompanied by the bigger activation of anaerobic metabolism with increase of lactate concentration in post-perfusion period (p < 0.01) which can be explained by less depression of the global metabolism by sevoflurane compared to desflurane.